2002
DOI: 10.1142/s0218625x02002816
|View full text |Cite
|
Sign up to set email alerts
|

SPIN-RESOLVED PHOTOELECTRON SPECTROSCOPY OF ULTRATHIN Fe FILMS ON GaAs(001)

Abstract: Thin epitaxial Fe films were grown on singular and vicinal GaAs(001) substrates, and their magnetic and electronic structures were investigated by synchrotron-based spin-resolved and spin-integrated photoelectron spectroscopy with different Fe thickness. There were two types of substrates: one was a Si-doped n-type GaAs(001) surface with doping concentration of 2 × 1018 cm -3 (singular substrate), and the other was orientated by 3° toward the (111)A direction (vicinal substrate). Spin polarization of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For example, we have found that Unfortunately, fitting to the different values of total momentum quantum number, J, is sensitive to M 0 . However we note that for thicker films the magnetic properties as measured by spin polarised photoelectron spectroscopy displayed bulk-like behaviour [13] and the values of Curie temperature are substantially higher than room temperature (please refer to Figure 4 and later discussions). We assume it to be a sensible estimation to use the magnetic asymmetry of 10nm Fe on a vicinal substrate (about 16%) as a measure of M 0 for the 0.9nm Fe on the vicinal substrate.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, we have found that Unfortunately, fitting to the different values of total momentum quantum number, J, is sensitive to M 0 . However we note that for thicker films the magnetic properties as measured by spin polarised photoelectron spectroscopy displayed bulk-like behaviour [13] and the values of Curie temperature are substantially higher than room temperature (please refer to Figure 4 and later discussions). We assume it to be a sensible estimation to use the magnetic asymmetry of 10nm Fe on a vicinal substrate (about 16%) as a measure of M 0 for the 0.9nm Fe on the vicinal substrate.…”
mentioning
confidence: 89%
“…Whilst recognising that the magnetic behaviour of ultrathin Fe layers is als o sensitive to both GaAs substrate surface morphology [12] and surface stoichiometry [13], this Letter reports on the temperature dependent magnetic state of Fe on GaAs(001) through a study of the magnetic dichroism of the Fe 2p and 3p core level photoelectrons with linearly polarised radiation.…”
mentioning
confidence: 97%
“…Investigations of thermal oxidation of gallium arsenide with transition metal nanofilms (in particular, iron, cobalt, and nickel nanofilms) deposited on the GaAs surface are of considerable interest [1][2][3][4][5][6][7][8][9][10][11][12]. This is associated with both the scientific interest and the significant practical importance, because it opens up new possibilities for combining valuable electrical, optoelectric, and unique magnetic properties in one material.…”
Section: Introductionmentioning
confidence: 99%